Sex differences in the predictability of risk-taking behavior. (13th December 2022) - Brand, Jack A; Henry, Jason; Melo, Gabriela C; Wlodkowic, Donald; Wong, Bob B M; Martin, Jake M
Abstract: Recent research has found that individuals often vary in how consistently they express their behavior over time (i.e., behavioral predictability) and suggested that these individual differences may be heritable. However, little is known about the intrinsic factors that drive variation in the predictability of behavior. Indeed, whether variation in behavioral predictability is sex-specific is not clear. This is important, as behavioral predictability has been associated with vulnerability to predation, suggesting that the predictability of behavioral traits may have key fitness implications. We investigated whether male and female eastern mosquitofish ( Gambusia holbrooki ) differed in the predictability of their risk-taking behavior. Specifically, over a total of 954 behavioral trials, we repeatedly measured risk-taking behavior with three commonly used assays—refuge-use, thigmotaxis, and foraging latency. We predicted that there would be consistent sex differences in both mean-level risk-taking behavior and behavioral predictability across the assays. We found that risk-taking behavior was repeatable within each assay, and that some individuals were consistently bolder than others across all three assays. There were also consistent sex differences in mean-level risk-taking behavior, with males being bolder across all three assays compared to females. In contrast, both the magnitude and direction of sex differences in behavioral predictability were assay-specific. Taken together, these results highlight that behavioral predictability may be independent from underlying mean-level behavioral traits and suggest that males and females may differentially adjust the consistency of their risk-taking behavior in response to subtle changes in environmental conditions. Abstract : Individuals often differ in how consistently they express their behavior (i.e., behavioural predictability). Recent research suggests that variation behavioral predictability is heritable and has key fitness consequences. We showed that male and female eastern mosquitofish ( Gambusia holbrooki ) differed in the predictability of their risk-taking behavior. Furthermore, we found that both the direction and magnitude of these sex differences were context specific.